Pengaruh Teknik Cognitive Behavior Therapy (CBT) Terhadap Pengalaman Traumatis Siswa Kelas VIII-A di UPTD SMP Negeri 1 Gunungsitoli Utara - Nisty Idasari Zega; Elizama Zebua (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study was to determine how much influence Cognitve Behavior Therapy (CBT) had in reducing the traumatic experience of Class VIII-A students at UPTD SMP Negeri 1 Gunungsitoli Utara. This study used a type of quantitative research-experiment with one group pretest-postest design. The data collection method uses questionnaires to determine students' traumatic experiences and observation data consisting of 3 observants to determine the match of statistical calculations with observation data. The pretest results of 26 students were obtained as many as 10 people experienced tarumatist experience and were determined as treatment subjects with a total of 227 gains. The results of the posttest calculation showed that there was a reduction in student trauma with an acquisition of as much as 80.  Based on the calculation of the O1-O2 difference, a result of 36.75% was obtained on a score of 16-30 with the criterion of "sufficient" which means there was a reduction in students' traumatic experiences after being given treatment and observation data showed that 67% were on the criteria of affecting students' traumatic experiences. Thus, the conclusion of the results of this study is that Cognitive Behavioral Therapy influences reducing students' traumatic experiences.